2017
DOI: 10.5056/jnm17022
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Delayed Colonic Transit Using Bristol Stool Form and Stool Frequency in Eastern Constipated Patients: A Difference From the West

Abstract: Background/AimsThe correlation between the Bristol stool form scale (BSFS) and colonic transit time (CTT) has been reported in Western populations. Our study aims to study the relationship between BSFS, stool frequency, and CTT in Eastern patients with chronic constipation. MethodsA total of 144 chronic functional constipation patients underwent colonic transit study by using radio-opaque markers, anorectal manometry, and balloon expulsion test. Stool diary including stool forms and frequency was recorded. Del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 39 publications
(59 reference statements)
0
33
0
1
Order By: Relevance
“…Whereas patients with constipation‐predominant IBS (IBS‐C) have slow gut, particularly colonic, transit, diarrhea‐predominant IBS (IBS‐D) patients have faster motility 1, 5, 19 . Multiple studies showed that Bristol stool form is determined by colonic motility; slower colon transit is associated with harder stools 20, 21 . Subsets of patients with IBS‐C as well as functional constipation have slow gut motility with or without associated fecal evacuation disorder 5 .…”
Section: Altered Gastrointestinal Motility In Irritable Bowel Syndromementioning
confidence: 99%
“…Whereas patients with constipation‐predominant IBS (IBS‐C) have slow gut, particularly colonic, transit, diarrhea‐predominant IBS (IBS‐D) patients have faster motility 1, 5, 19 . Multiple studies showed that Bristol stool form is determined by colonic motility; slower colon transit is associated with harder stools 20, 21 . Subsets of patients with IBS‐C as well as functional constipation have slow gut motility with or without associated fecal evacuation disorder 5 .…”
Section: Altered Gastrointestinal Motility In Irritable Bowel Syndromementioning
confidence: 99%
“…Thus, the correlation of BSFS with IBS classification in Asian patients may be different from that in the West. [120][121][122] Statement 19: The diagnosis of IBS requires careful history taking with reference to the diagnostic criteria of IBS, physical examination, and investigations may be performed if indicated, but there is no single diagnostic or confirmatory test for IBS.…”
Section: Team 2: Pathophysiologymentioning
confidence: 99%
“…Colon transit time is known to correlate inversely with Bristol stool forms; shorter transit time is associated with higher scores [ 18 ]. Accordingly, the Indian patients have softer stools than the patients from the West, for example the USA [ 19 ].…”
Section: Consensus Statementsmentioning
confidence: 99%